COMPARISON OF K-NEAREST NEIGHBORS AND NAÏVE BAYES CLASSIFIER ALGORITHMS IN SENTIMENT ANALYSIS OF USER REVIEWS FOR INTERMITTENT FASTING APPLICATIONS - Kusuma, Muhammad Varhan; Juanita, Safitri (Informatika, Universitas Jenderal Soedirman, 2024)
Applications that focus on health, especially obesity prevention, are scattered in the Google Play Store, one of which is the